Checklist for the genus Luisia and a new species (Luisia, Orchidaceae) from Southern Vietnam - Vu , Kim Cong; Quach, Van Hoi; Dang, Thi Tham; Tran, Thai Vinh; Nong, Van Duy (Academia Journal of Biology, 2024)
Recently, there have been some reports on new species of the genus Luisia in Vietnam. There is disagreement among studies on the number of species in this genus. Our study gathers available documents and samples from herbariums in order to tally and classify them. Research results have recorded 13 species of the Luisia genus in Vietnam. The study also describes one taxon as a new species. A taxonomic key for the identification of all species of the Luisia genus known in Vietnam is also established. The study will be a useful reference for classification as well as the identification and description of new species belonging to the genus Luisia.